Target detection on the ocean with the relative phase of compact polarimetry SAR - Li, Haiyan; Perrie, William; He, Yijun; Lehner, Susanne; Brusch, Stephan (IEEE Transactions on Geoscience and Remote Sensing, 2013)
This paper discusses the potential for automatic ocean surveillance using compact linear polarization (CL-pol) synthetic aperture radar (SAR), with large area coverage. Here, the target is a wind farm in the North Sea. The relative phase, as derived from CL-pol SAR, is employed for detection of the wind turbines, apart from the wind turbines' wakes, based on fine-mode quad-polarization (quad-pol) RADARSAT-2 (RS-2) images. The relative phase of CL-pol measurements improves the contrast between the wind turbines and their wakes, because it has opposite signs for these two entities. Moreover, there is almost no variation in the relative phase with respect to wind speed or incidence angle. The results are verified by high-sea-state cases, up to 8.7-m significant wave height and 24.3-m/s wind speed, and also 641 quad-pol RS-2 SAR images collocated with 52 National Data Buoy Center buoys at different incidence angles and sea states. Thus, the relative phase of CL-pol SAR provides new light into the problem of operational autodetection of man-made targets, under high-sea-state conditions, over large areas. © 1980-2012 IEEE.
CRIS-Team Scopus Importer:2024-03-18
Keywords: Compact polarimetric SAR; relative phase of orthogonal electric field components; stokes parameters; target detection